Modeling cost‐effectiveness and health gains of a "universal" versus "prioritized" hepatitis C virus treatment policy in a real‐life cohort. Issue 6 (30th October 2017) - Kondili, Loreta A.; Romano, Federica; Rolli, Francesca Romana; Ruggeri, Matteo; Rosato, Stefano; Brunetto, Maurizia Rossana; Zignego, Anna Linda; Ciancio, Alessia; Di Leo, Alfredo; Raimondo, Giovanni; Ferrari, Carlo; Taliani, Gloria; et al.
Abstract : We evaluated the cost‐effectiveness of two alternative direct‐acting antiviral (DAA) treatment policies in a real‐life cohort of hepatitis C virus–infected patients: policy 1, "universal, " treat all patients, regardless of fibrosis stage; policy 2, treat only "prioritized" patients, delay treatment of the remaining patients until reaching stage F3. A liver disease progression Markov model, which used a lifetime horizon and health care system perspective, was applied to the PITER cohort (representative of Italian hepatitis C virus–infected patients in care). Specifically, 8, 125 patients naive to DAA treatment, without clinical, sociodemographic, or insurance restrictions, were used to evaluate the policies' cost‐effectiveness. The patients' age and fibrosis stage, assumed DAA treatment cost of €15, 000/patient, and the Italian liver disease costs were used to evaluate quality‐adjusted life‐years (QALY) and incremental cost‐effectiveness ratios (ICER) of policy 1 versus policy 2. To generalize the results, a European scenario analysis was performed, resampling the study population, using the mean European country‐specific health states costs and mean treatment cost of €30, 000. For the Italian base‐case analysis, the cost‐effective ICER obtained using policy 1 was €8, 775/QALY. ICERs remained cost‐effective in 94%‐97% of the 10, 000 probabilistic simulations. For the European treatment scenario the ICER obtained using policy 1 was €19, 541.75/QALY. ICER was sensitive to variations in DAA costs, in the utility value of patients in fibrosis stages F0‐F3 post–sustained virological response, and in the transition probabilities from F0 to F3. The ICERs decrease with decreasing DAA prices, becoming cost‐saving for the base price (€15, 000) discounts of at least 75% applied in patients with F0‐F2 fibrosis. Conclusion : Extending hepatitis C virus treatment to patients in any fibrosis stage improves health outcomes and is cost‐effective; cost‐effectiveness significantly increases when lowering treatment prices in early fibrosis stages. (Hepatology 2017;66:1814–1825)